Cu-isotope evidence for subduction modification of lithospheric mantle - Kempton, Pamela; Mathur, Ryan; Harmon, Russell S.; Bell, Aaron; Hoefs, Jochen; Shaulis, Barry (My University, 2022)
A. Filename: 2021GC010134_Table_S1_probe_data_silicates.xlsx Short description: Excel file containing major element mineral compositions for silicate minerals (olivine, clinopyroxene, orthopyroxene, phlogopite and amphibole) in GVF ultramafic xenoliths determined by electron microprobe analysis B. Filename: 2021GC010134_Table_S1_probe_data_silicates.pdf Short description: pdf version of the Excel file described in (A) C. Filename: 2021GC010134_Table_S2_probe_data_nonsilicates.xlsx Short description: Excel file containing major element mineral compositions for nonsilicate minerals (spinel, sulfides, FeTi oxides) in GVF ultramafic xenoliths determined by electron microprobe analysis D. Filename: 2021GC010134_Table_S2_probe_data_nonsilicates.pdf Short description: pdf version of the Excel file described in (C) E. Filename: 2021GC010134_Table_S3_mineral_trace_elements.xlsx Short description: Excel file containing mineral trace element analyses (clinopyroxene, orthopyroxene, olivine, amphibole, and glass) determined on hand-picked mineral separates by Instrumental Neutron Activation Analysis (INAA) and in situ Laser-Assisted Inductively Coupled Mass Spectrometry on thin sections (LA-ICPMS) F. Filename: 2021GC010134_Table_S3_mineral_trace_elements.pdf Short description: pdf version of the Excel file described in (E) G. Filename: 2021GC010134_Table_S4_Cu_isotope_rock_standard_data.xlsx Short description: Excel file containing the Cu isotope compositions of rock standard BHVO-2 run during the project. H. Filename: 2021GC010134_Table_S4_Cu_isotope_rock_standard_data.pdf Short description: pdf version of the Excel file described in (G) I. Filename: 2021GC010134_Table_S5_WR_major_and_trace_elements.xlsx Short description: Excel file containing whole rock major and trace element analyses determined by XRF and LA-ICPMS for GVF ultramafic peridotites J. Filename: 2021GC010134_Table_S5_WR_major_and_trace_elements.pdf Short description: pdf version of the Excel file described in (I)
A. Filename: 2021GC010134_Table_S1_probe_data_silicates.xlsx Short description: Excel file containing major element mineral compositions for silicate minerals (olivine, clinopyroxene, orthopyroxene, phlogopite and amphibole) in GVF ultramafic xenoliths determined by electron microprobe analysis B. Filename: 2021GC010134_Table_S1_probe_data_silicates.pdf Short description: pdf version of the Excel file described in (A) C. Filename: 2021GC010134_Table_S2_probe_data_nonsilicates.xlsx Short description: Excel file containing major element mineral compositions for nonsilicate minerals (spinel, sulfides, FeTi oxides) in GVF ultramafic xenoliths determined by electron microprobe analysis D. Filename: 2021GC010134_Table_S2_probe_data_nonsilicates.pdf Short description: pdf version of the Excel file described in (C) E. Filename: 2021GC010134_Table_S3_mineral_trace_elements.xlsx Short description: Excel file containing mineral trace element analyses (clinopyroxene, orthopyroxene, olivine, amphibole, and glass) determined on hand-picked mineral separates by Instrumental Neutron Activation Analysis (INAA) and in situ Laser-Assisted Inductively Coupled Mass Spectrometry on thin sections (LA-ICPMS) F. Filename: 2021GC010134_Table_S3_mineral_trace_elements.pdf Short description: pdf version of the Excel file described in (E) G. Filename: 2021GC010134_Table_S4_Cu_isotope_rock_standard_data.xlsx Short description: Excel file containing the Cu isotope compositions of rock standard BHVO-2 run during the project. H. Filename: 2021GC010134_Table_S4_Cu_isotope_rock_standard_data.pdf Short description: pdf version of the Excel file described in (G) I. Filename: 2021GC010134_Table_S5_WR_major_and_trace_elements.xlsx Short description: Excel file containing whole rock major and trace element analyses determined by XRF and LA-ICPMS for GVF ultramafic peridotites J. Filename: 2021GC010134_Table_S5_WR_major_and_trace_elements.pdf Short description: pdf version of the Excel file described in (I)